Computational insights into electronic, magnetic and optical properties of Mn(II)-doped ZnTe with and without vacancy defects. (1st November 2022) - Khan, Muhammad Sheraz; Shi, Li-Jie; Abdalla, A.S.; Zou, Bingsuo; Ikram, Muhammad
Abstract: First principles calculations have been performed to investigate the optoelectronic and magnetic properties of Mn(II); ZnTe DMS with and without native defects using first principle calculations. Our results find that anti-ferromagnetic coupling dominates in the pure Mn(II)-doped ZnTe system due to super-exchange (SE) mechanism. The impact of p-type and n-type defects on magnetic coupling in Mn(II)-doped ZnTe were discussed and we found that p-type defect such as Zn vacancy defects play important role in stabilization of FM state due to the formation of bound magnetic polaron (BMP) while n-type defect such as Te vacancy defect does not affect the ground state of Mn(II); ZnTe. The magnetic coupling of Mn(II) spins in the absence and presence of Zn vacancy were explained on the basis of phenomenological band structure model. The optical absorption spectra of pure ZnTe and Mn(II); ZnTe with and without vacancies have been investigated and we found that single Mn(II)-doping in the lattice of ZnTe generates an absorption band at energy around 2.02 eV, which is assigned to intra-band d-d transitions of Mn(II) dopant. The band at energy around 0.44 eV in the absorption spectrum of Mn(II)-doped ZnTe with Zn-vacancy may be due to the acceptor states produced by Zn vacancy at Fermi level and band around 1.6 eV in the spectrum of Te vacancy defect system are related to the donor states produced by Te vacancy defect. Moreover, the correlation of magnetic coupling with intra-band d-d transition bands and fundamental bandgaps of ZnTe were also discussed and it was found that intra-band transition peak of Mn(II) ions and optical band gap of ZnTe are blue-shift in AFM coupled Mn(II) ions and are red-shift in FM coupled ions system. Our present findings highlight the worthwhile half-metallic properties of Mn(II)-doped ZnTe, which can be obtained via Zn vacancy defect engineering; this can find broad applications for the fabrication of optoelectronic and spintronic devices. Graphical abstract: Image 1 Highlights: The coupling between Mn(II) spins is antiferromagnetic in the lattice of ZnTe in the absence of vacancy defects. Zn vacancy changes the ground state of Mn(II)-doped ZnTe from AFM to FM. Te vacancy has no effect on the ground state of Mn(II)-doped ZnTe. The optical absorption edge of Mn(II); ZnTe is attributed to the d-d transition of Mn-ion. The d-d transition peaks and bandgap of ZnTe are blue/red shifted in AFM and FM configurations.